Giving a voice to the best faculty members: benefits of digital resources for the inclusion of all students in Arts and Humanities - Cotán, Almudena; Carballo, Rafael; Spinola-Elias, Yolanda (Routledge, 2022)
This article presents the testimonies of 24 faculty members of Arts and Humanities from five Spanish universities on the use of digital technology resources and their benefits for learning and educational inclusion of students with disabilities. They were selected by their own students with disabilities for their inclusive practices. Using a qualitative methodology, two semi-structured individual interviews were conducted with each participant to analyse different areas of inclusive pedagogy: beliefs, knowledge, designs and actions. The data were progressively analysed through a system of categories and inductive codes. The results show the digital resources that faculty members put into practice, as well as the different uses they make of them. In addition, the participants highlighted a number of benefits that digital technology has for the learning of all students, including those with disabilities. Finally, these results are discussed with those of previous studies, offering recommendations for the university to move toward a more inclusive education.
Keywords: Arts and Humanities; educational technologies; faculty members; higher education; inclusive pedagogy; Scopus; JCR